2011
DOI: 10.1111/j.1442-2042.2011.02767.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a liquid fibrin sealant with sheet‐type hemostatic agents: Experimental evaluation in partial nephrectomy animal model

Abstract: Liquid fibrin sealants, together with sheet-type hemostatic agents, have been used during partial nephrectomies to secure effective hemostasis at the suture site. Using animal kidneys, we investigated which hemostatic agent might adhere most effectively to the renal tissue and serve best as a bolster. Liquid fibrin sealant alone, or in combination with a sheet-type hemostat, such as collagen, gelatin or oxidized-cellulose hemostat, was applied to the cut surface of the kidney of anesthetized rabbits, and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Following this study, we have performed an in vivo experiment with live rabbits as a partial nephrectomy model testing the fibrin glue and several hemostatic agents, and demonstrated that the adhesive capability of the fibrin glue is superior when combined with a collagen or gelatin hemostat. 15 …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Following this study, we have performed an in vivo experiment with live rabbits as a partial nephrectomy model testing the fibrin glue and several hemostatic agents, and demonstrated that the adhesive capability of the fibrin glue is superior when combined with a collagen or gelatin hemostat. 15 …”
Section: Resultsmentioning
confidence: 97%
“…10 There have been few reports comparing the effects of using a combination of hemostatic agents and fibrin glue, however. 15 In Experiments A and B, we investigated the difference in the degree of adhesion of the sealants used-namely, a combination of fibrin glue plus sheet-type collagen, gelatin, or oxidized cellulose hemostat-to the kidney tissue. (1) In the collagen hemostat group, the glue was equally distributed among the fibers over a large area, including in the region of its contact with the renal tissue as the fibrin gel (arrow).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of sealants in our case was critical to obtain a success of treatment with the purpose of decreasing the defects of parenchyma, filling in the cavity and avoiding a large contact with the urine that could compromise the polymerization of glue. Ishii K. et al in a PN animal model study demonstrated that fibrin sealant plus the collagen or gelatin hemostat have a stronger hemostatic effect than fibrin sealant applied alone (10). The histological investigation showed that the fibrin sealant adhered well to kidney tissue when it was applied with the collagen or gelatin hemostat, showing the advantage of combining these two materials for achieving effective hemostasis and closure effect.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In a porcine animal study, the time to achieve hemostasis after surgically induced liver trauma was significantly reduced when the polyurethane‐based adhesive was used compared to trials where fibrin sealants were used 38 . In terms of achieving hemostasis, the combination of the adhesive with classical hemostats like oxidized cellulose, gelatin or collagen sponge might be a promising approach 39,40 …”
Section: Discussionmentioning
confidence: 99%